Moisture Adsorption Isotherms and Thermodynamic Properties of Penaeus vannamei Meat with and without Maltodextrin Addition. Issue 8 (16th November 2016) - Shi, Qilong; Lin, Wenwen; Zhao, Ya; Zhang, Pingping; Wang, Ruiying
ABSTRACT: Moisture adsorption isotherms of freeze-dried Penaeus vannamei meat containing maltodextrin (PV-MD) and maltodextrin-free (PV) samples were determined at temperatures of 5, 15, 25, 35, and 45°C with water activity ( a w ) ranging from 0.112 to 0.931. The adsorption behaviors of PV and PV-MD followed type III isotherms. The equilibrium moisture content of PV and PV-MD decreased with increasing temperature and increased with increasing a w . The monolayer moisture content increased with the addition of maltodextrin and was observed to be 0.0611–0.0824 and 0.0734–0.1034 g water/g dry solids for PV and PV-MD, respectively. Eight models were employed to fit experimental data, and the Guggenheim-Anderson-de Boer (GAB) model achieved the best fit. For both PV and PV-MD, the differential enthalpy and entropy and integral enthalpy decreased with increasing moisture content. The integral entropy was negative in value and increased with increasing moisture content. The spreading pressure increased with increasing a w but decreased with increasing temperature. A plot of differential enthalpy versus entropy satisfied the enthalpy-entropy compensation theory, and the adsorption behavior of P. vannamei meat was enthalpy-driven and spontaneous. Addition of maltodextrin increased the differential enthalpy and entropy, integral enthalpy, and spreading pressure, but decreased the integral entropy of P. vannamei meat.